2014
DOI: 10.1126/scitranslmed.3009569
|View full text |Cite
|
Sign up to set email alerts
|

Denervation suppresses gastric tumorigenesis

Abstract: The nervous system plays an important role in the regulation of epithelial homeostasis and has also been postulated to play a role in tumorigenesis. We provide evidence that proper innervation is critical at all stages of gastric tumorigenesis. In three separate mouse models of gastric cancer, surgical or pharmacological denervation of the stomach (bilateral or unilateral truncal vagotomy, or local injection of botulinum toxin type A) markedly reduced tumor incidence and progression, but only in the denervated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
534
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 484 publications
(570 citation statements)
references
References 56 publications
(81 reference statements)
14
534
1
2
Order By: Relevance
“…Autonomic neurotransmitters can also stimulate endothelial cells, immune cells, and fibroblasts thus having an impact on the tumour microenvironment [51]. Moreover, it has recently been reported that nerves in prostate and gastric tumours, release neurotransmitters directly into the vicinity of cancer cells to stimulate survival, proliferation, and the ability to spread [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic neurotransmitters can also stimulate endothelial cells, immune cells, and fibroblasts thus having an impact on the tumour microenvironment [51]. Moreover, it has recently been reported that nerves in prostate and gastric tumours, release neurotransmitters directly into the vicinity of cancer cells to stimulate survival, proliferation, and the ability to spread [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…They proposed that sympathetic postganglionic neurons regulated the initiation of the disease, whereas postganglionic parasympathetic neurons were implicated in advanced disease. Zhao et al (52), used three models of gastric cancer and found that surgical vagotomy slowed and/or decreased tumor progression and increased the effectiveness of chemotherapy. Parasympathetic postganglionic neurons were also implicated based on changes in signaling pathways downstream of the type 3 muscarinic receptor expressed by these neurons, and that botox was able to slow tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…In three independent mouse models of gastric cancer, Zhao et al elegantly demonstrated that surgical or pharmacological denervation suppresses gastric tumorigenesis, even if performed at an early preneoplastic step [21]. Further analyses revealed that cholinergic nerves surround the base of glands and modulate epithelial stem cells through activation of the Wnt signaling pathway via the muscarinic acetylcholine receptor 3 (M 3 R) expressed by Lgr5 + cells.…”
Section: Factors Sustaining Gastric Stem Cell Self-renewal and Multipmentioning
confidence: 99%
“…The Notch signaling pathway is also inhibited in vagotomized mice [21]. The Notch inhibitor dibenzazepine (DBZ) reduced the proliferation in the isthmus region, decreased the Mist1-lineage tracing, and blocked the growth of corpus organoids in vitro, suggesting that Notch activity is important for corpus gastric stem cell maintenance and activity [13].…”
Section: Factors Sustaining Gastric Stem Cell Self-renewal and Multipmentioning
confidence: 99%
See 1 more Smart Citation